2013
DOI: 10.1108/emjb-05-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

Cost of capital in SMEs

Abstract: Purpose -The purpose of this paper is to discuss the applicability of value based management (VBM) concepts for small to medium-sized enterprises (SMEs) and to identify obstacles for its implementation. Estimating cost of capital is central to all VBM concepts, it is hence intended to critically analyse approaches that allow estimating cost of capital for non-publicly traded firms. Design/methodology/approach -The paper is based on literature review and a case study approach. A case study on estimating the cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Ward (1999) agrees that this method is widely used to calculate cost of capital. In Britzelmaier et al (2013) paper it is written that 75 % of financial professors suggest using CAPM to estimate cost of equity capital with regard to capital budgeting. Despite it's popularity, researchers express concern towards eligibility of CAPM.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Ward (1999) agrees that this method is widely used to calculate cost of capital. In Britzelmaier et al (2013) paper it is written that 75 % of financial professors suggest using CAPM to estimate cost of equity capital with regard to capital budgeting. Despite it's popularity, researchers express concern towards eligibility of CAPM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In economic terms, it is the rate of return needed to make capital investment worthwhile, taking into account cost of alternative investment methods (Barth, 2009). Although large enterprises for managerial practices use WACC less frequently after the financial crisis, which began in 2008, capital cost measurement and use as a motivational device is still widely employed in small and medium size companies (Britzelmaier et. al., 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For small businesses however, this information may not be available. Several authors have suggested the use of alternative forms of beta calculation in order to work around this issues, such as the use of accounting betas, based on the historic accounting returns of the small business (Almisher and Kish 2000;St-Pierre and Bahri 2006) and the use of pure-play betas, based on market benchmarks of listed companies in similar industries (Bernd Britzelmaier et al 2013;Collier et al 2007;Fuller and Kerr 1981). Agency cost within small businesses (which is usually PP in nature) has an indirect impact on small business risk and by calculating the cost of capital for small businesses, the value of small business risk and its PP conflict exposure can be estimated.…”
Section: Large German Family Firmsmentioning
confidence: 99%
“…Fred Weston, 1996) Seeing the development of MSMEs that continues to increase from year to year, this has not been accompanied by awareness of MSMEs actors in understanding and the importance of analyzing capital structure for their business activities. The use of capital structures in the MSME sector still tends to often use external sources of debt (Debt) which cause high costs of capital to be borne rather than using funding sources originating from internal sources, so that simple and easy to understand analysis is needed to help optimize the extent to which the business can using the composition of the right capital structure (Optimal) using the Weighted Average Cost Of Capital (WACC) analysis method (Britzelmaier, Kraus, Häberle, Mayer, & Beck, 2013). Weighted Average Cost Of Capital is the weighted average cost of capital for all financing sources that the company will use to finance long-term assets (David F. Scott, 2000).…”
Section: Introductionmentioning
confidence: 99%